Sudden death in a patient with severe mitral annular calcification and end-stage renal disease during hemodialysis: A case report. Issue 26 (June 2018) - Xing, Jingjun; Wang, Ke; Wei, Hua; Jiang, Wenwen; Wei, Dengming
Abstract: Rationale: Mitral annular calcification (MAC) is a chronic, degenerative cardiac condition. Although MAC is often considered as an incidental finding in clinical and forensic practice, sudden death due to severe MAC with end-stage renal disease (ESRD) during hemodialysis is uncommon. In addition, spontaneous subepicardial hematoma due to rupture of the subepicardial vein is very rare. Patient concerns: A 65-year-old woman had a history of hypertension, diabetes mellitus, and renal failure. Diagnoses: Postmortem examination revealed marked MAC with cardiomegaly and ESRD. Spontaneous subepicardial hematoma due to disruption of subepicardial vein was also seen. Interventions and outcomes: The patient became short of breath while on hemodialysis and expired en route to the hospital. Lessons: In this case, death was attributed to the effects of the calcified mitral valve annulus. This case highlights that MAC must be considered in any patient with ESRD and fatal cardiovascular events should not be overlooked in these patients.